The Election Supervisory Agency’s Political Mitigation Against Religious Polarization in Regional Head Elections: A Study of Democratic Transcendence - Nuria Siswi, Enggarani; Farid, Achmad Miftah (Journal of Transcendental Law, 2024)
Regional Head Elections in Indonesia are often colored with religious polarization, which becomes a challenge for democracy and may potentially trigger conflicts. The Election Supervisory Agency holds a crucial role in mitigating this polarization. This research aims to analyze the Election Supervisory Agency’s political mitigation model against religious polarization in Regional Head Elections. Using the qualitative approach with the doctrinal method, this research analyzed legal regulations and democratic principles related to the general election as well as analyze the Election Supervisory Agency’s role in handling religious polarization. Research results showed that religious polarization in Regional Head Elections is manifested in several forms, such as using issues related to ethnic groups, religion, race, and groups in campaigns, spreading religion-related hoaxes and hate speech, as well as mass mobilization based on religious sentiments. Even though the Election Supervisory Agency has a supervisory mandate, it faces limitations in handling religious polarization. This issue is often under the scope of political ethics, which is not specifically regulated in the General Election Law. The analysis also shows that democratic and religious principles, especially those of Islam, support deliberation and dialogs, which may become a base for mitigating polarization. This research concludes that the Election Supervisory Agency needs to develop a more comprehensive political mitigation strategy which involves cooperation with various parties and strengthens the public understanding of political and democratic ethics. This research recommends the expansion of the Election Supervisory Agency's authority in handling violations against political ethics, strengthening coordination with other institutions, and increasing society's political literacy.